Parents' past bonding experience with their parents interacts with current parenting stress to influence the quality of interaction with their child - Azhari, Atiqah (2020)
Healthy dyadic interactions serve as a foundation for child development and are typically characterised by mutual emotional availability of both the parent and child. However, several parental factors might undermine optimal parent-child interactions, including the parent's current parenting stress levels and the parent's past bonding experiences with his/her own parents. To date, no study has investigated the possible interaction of parenting stress and parental bonding history with their own parents on the quality of emotional availability during play interactions. In this study, 29 father-child dyads (18 boys, 11 girls; father's age = 38.07 years, child's age = 42.21 months) and 36 mother-child dyads (21 boys, 15 girls; mother's age = 34.75 years, child's age = 41.72 months) from different families were recruited to participate in a 10-min play session after reporting on their current parenting stress and past care and overprotection experience with their parents. We measured the emotional availability of mother-child and father-child play across four adult subscales (i.e., sensitivity, structuring, non-intrusiveness, non-hostility) and two child subscales (i.e., involvement and responsiveness). Regression slope analyses showed that parenting stress stemming from having a difficult child predicts adult non-hostility, and is moderated by the parents' previously experienced maternal overprotection. When parenting stress is low, higher maternal overprotection experienced by the parent in the past would predict greater non-hostility during play. This finding suggests that parents' present stress levels and past bonding experiences with their parents interact to influence the quality of dyadic interaction with their child.